Amagada, perseguida y ¿sometida? Discurso satírico-visual y normativa legal sobre la libertad de imprenta. Ciudad de México, 1868-1883 - Gantús, Fausta (El Colegio de México, A.C., 2019)
Situated in the intersection between satirical visual representations and the regulatory framework on the freedom of the press between 1868 and 1883, this article reflects on the dynamic relationship between journalism and politics, studying the political cartoons published during this period, as well as laws and various legal provisions – regulations, constitutional reforms, decrees, circulars, etc. The tensions between the press and government authorities are duly studied herein with the goal of showing the complexity of the issue, the diversity of actors that intervened in this process, the many difficulties it presents and the varied perspectives from which it can be addressed, thus overcoming the traditional dichotomous vision of repressive government/independent press. Extraordinary powers, the suspension of guarantees, press laws, the reform of Article 7 of the Constitution, censorship strategies (both legal and extralegal) and mechanisms of repression (both formal and informal, some of them marked by the use of physical violence) are examined in order to understand debates and developments in the defense of and attack on the freedom of the press as part of the search to regulate and delimit the margins of expression. The roles played by the executive, legislative and judicial branches in these dynamics are also studied and analyzed in this article. The appendices include a chronological account of the laws and legal provisions in place at each time, as well as of the reform of Article 7 of the Constitution; this information has never before been systematized, yet it is essential to understanding the legal context for the freedom of the press.